Preparation method of layered composite material and layered composite material
By introducing copper as an intermediate layer in the magnesium-tantalum metal composite material, the interface structure is optimized, and the problems of process complexity and interface stability in the prior art are solved, and higher electromagnetic shielding and conductive properties are achieved.
Patent Information
- Application Number
- CN202411931042.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The existing magnesium and tantalum metal composite materials have complex processes and the risk of brittle intermetallic compounds at the Mg/Al interface, affecting performance stability.
Copper is used as the intermediate layer, and the interface regulation process optimization is used to form a multi-layer heterogeneous interface to achieve better electromagnetic shielding resistance and expand the protection coverage of magnesium-based alloys.
It achieves higher electromagnetic shielding resistance, good radiation resistance and excellent conductivity, while improving interface bonding strength and enhancing the overall performance of the material.
Smart Images

Figure CN119748988A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and particularly relates to a preparation method of a layered composite material and the layered composite material. Background Art
[0002] The rapid development of deep space exploration, green transportation, intelligent manufacturing and other fields has put forward new urgent demands for new structural and functional integrated materials. For lightweight metal structural materials, new requirements are put forward for corrosion resistance, electromagnetic shielding resistance, radiation resistance, etc. on the premise of ensuring mechanical properties. However, a single metal cannot meet the above requirements, and the combination of different metal materials to give full play to the advantages of different materials and achieve complementary advantages of structural and functional characteristics is an important direction of current material development.
[0003] Magnesium is the lightest metal structural material. In order to meet the requirements of radiation resistance, electromagnetic shielding resistance, corrosion resistance and high conductivity, heavy metals such as tantalum, niobium, and tungsten with excellent corrosion resistance, radiation resistance and electromagnetic shielding resistance are combined with magnesium, thereby realizing the extended application of high-energy particle radiation resistance and electromagnetic shielding in deep space exploration, green transportation and other fields, while greatly reducing the launch cost of detectors and improving the service life of devices. Research on electromagnetic shielding composite material systems shows that Mg / Ta composite materials have excellent electromagnetic shielding effects and can significantly reduce the overall weight of the shielding device (Wang Jianzhao, Ma Jinan, Zhang Qingxiang, et al. Radiation shielding optimization design method of multilayer materials in Jupiter system exploration [J]. Spacecraft Environment Engineering, 2019, 36(6).).
[0004] The Chinese invention patents with publication numbers CN115742485A and CN 115740002A disclose a magnesium-tantalum metal composite method based on Al as an intermediate layer. However, the process involves the use of an aluminum plate covered with B4C ceramic particles on the surface, the plate being immersed in liquid nitrogen for deep cryogenic treatment, and high-temperature diffusion annealing treatment. The overall process flow is relatively complicated, and due to the introduction of the Al layer, Mg is generated at the Mg / Al interface during hot working and high-temperature diffusion annealing. 17 Al 12 The risk of brittle intermetallic compounds such as Mg2Al3 poses a potential threat to the performance stability of the composite plate. Summary of the invention
[0005] In view of the deficiencies in the above-mentioned prior art, the present invention provides a method for preparing a layered composite material and a layered composite material, innovatively introducing highly conductive copper as an intermediate layer, and forming a multilayer heterogeneous interface through interface regulation process optimization, which can effectively scatter and lose electromagnetic waves to achieve more excellent electromagnetic shielding performance, and has the good radiation resistance of metal tantalum itself, thereby greatly expanding the protection coverage of magnesium-based alloys. At the same time, it has better conductivity than conventional magnesium alloys, and the first plate, the second plate and the third plate are strong and plastic matching, thereby improving the interface bonding strength.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] On the one hand, the present invention provides a method for preparing a layered composite material, comprising the following steps: stacking an annealed first plate, a second plate and a third plate to form a minimum unit, wherein the first plate is an HCP structure, the second plate is an FCC structure, the third plate is a BCC structure, and the second plate is located between the first plate and the third plate; the tensile strength of the second plate is 150-300 MPa; the thickness ratio of the first plate, the second plate and the third plate satisfies 20:(1-2):(10-15), and the thickness of the second plate is 0.05-0.80 mm; rolling the minimum unit, and the reduction amount of the first rolling is 50%-75%.
[0008] Furthermore, the minimum unit is preheated before rolling, and is coated with aluminum foil at a holding temperature of 150-350° C. for a holding time of 15-35 minutes.
[0009] Furthermore, the first plate is one or more of AZ31, AZ91, ZK60 / 61, and Mg-RE series alloy plates; and / or the second plate is one or more of copper or copper alloys; and / or the third plate is tantalum.
[0010] Furthermore, the minimum unit is arranged in the following order: first plate|second plate|third plate|second plate|first plate.
[0011] Furthermore, the minimum unit is subjected to subsequent rolling passes no more than twice, and the single rolling reduction is 10%-20%; the minimum unit after the first rolling is stacked and then rolled, and the stacking and rolling are repeated no more than five times, and the rolling reduction is 50%-65%.
[0012] Furthermore, the smallest unit after the first rolling is stacked at 90 degrees and then rolled, and the stacking and rolling are repeated for no more than five times and each time the stacking is at 90 degrees, and the rolling reduction is 55%-65%.
[0013] Furthermore, the rolling speeds of the first rolling pass, subsequent rolling passes and overlapping rolling are 0.015-0.05 m / s, and the rolling roll temperature is 150-350°C.
[0014] Furthermore, before the lamination, the surface of the composite material of the first rolling or the previous lamination is polished, and then heated in a vacuum environment or an inert gas atmosphere, the heating temperature is 300-350° C., and the insulation time is 10-20 minutes.
[0015] Furthermore, the first plate and the third plate after annealing are ground, including grinding in the rolling direction and transverse direction, and the transverse and longitudinal surface roughness Ra after grinding is 5-15 μm.
[0016] The present invention also provides a layered composite material, which is prepared by the above-mentioned preparation method.
[0017] Compared with the prior art, the technical solution provided by the present invention brings the following beneficial effects:
[0018] The present application controls the crystal structure of the material, the tensile strength of the second plate, the thickness ratio of the first plate to the third plate, and combines with the subsequent rolling process, so that the first plate and the third plate, which have huge differences in structure and physicochemical properties and are difficult to directly form an atomic interdiffusion interface, can achieve strong-plastic matching by introducing the second plate, thereby forming a strongly bonded endogenous deep corrugated structure interface. That is, from a macroscopic point of view, the interfaces are staggered and the mechanical bonding strength is high. From a microscopic point of view, the interfaces are mutually embedded or meshed, achieving cross-scale mechanical meshing and interlocking, so that the mechanical bonding strength of the bonding interface is high. This interface is the optimal result pursued in the preparation of layered composite materials by rolling methods. In particular, the microscopically staggered interface is the main reason for the high interface bonding strength under variable temperature and the lack of cracks. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0020] Figure 1 This is a SEM image of the layered composite material prepared in Example 1 of the present invention;
[0021] Figure 2 This is a SEM image of the layered composite material prepared in Example 5 of the present invention;
[0022] Figure 3is a macroscopic image of the layered composite material prepared in Comparative Example 1;
[0023] Figure 4 This is a phase diagram of the layered composite material prepared in Comparative Example 2, where a is a macroscopic morphology diagram and b is a microscopic morphology diagram. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. The specific implementation of the present invention is not limited to the specific embodiments given here, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the disclosed specific embodiments.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and do not limit the present invention.
[0026] The present invention provides a method for preparing a layered composite material, comprising the following steps:
[0027] S1 stacks the annealed first plate, the second plate and the third plate to form a minimum unit, wherein the first plate is an HCP structure, the second plate is an FCC structure, the third plate is a BCC structure, and the second plate is located between the first plate and the third plate; the tensile strength of the second plate is 150-300 MPa; the thickness ratio of the first plate, the second plate and the third plate satisfies 20:(1-2):(10-15), and the thickness of the second plate is 0.05-0.80 mm;
[0028] S2: rolling the minimum unit, and the reduction amount of the first rolling is 50%-75%.
[0029] The present application achieves strength-plastic matching among the first plate, the second plate and the third plate by controlling the crystal structure of the material, the tensile strength of the second plate, the thickness ratio of the first plate to the third plate, and combining with a subsequent rolling process, and a deep corrugated structure appears at the bonding interface. That is, from a macroscopic point of view, the interfaces are jagged and have a high mechanical bonding strength, and from a microscopic point of view, the interfaces are also jagged and have a high mechanical bonding strength. This kind of interface is the optimal result pursued in preparing layered composite materials by rolling methods. First, the HCP crystal type has only 4 independent slip systems, which makes it difficult to slip in multiple directions, so the plastic deformation ability is poor; the BCC crystal has 48 independent slip systems, which makes it easy to slip in multiple directions, so it has a higher plastic deformation ability. Therefore, due to the poor strength-plastic matching of these two crystal types during the rolling process, when the atomic diffusion interface cannot be formed, even under large deformation conditions, the interface between the two cannot have a deep corrugated structure. The reason is that the BCC crystal is easy to deform during the deformation process, and the interface with the HCP crystal type with high processing difficulty cannot be kneaded to form a deep corrugated structure, so the bonding strength is low, and the interlayer tearing strength is low. Usually, metallurgical bonding and mechanical bonding are required to work together to realize a layered composite material that can be engineered for application. Only by adding the second plate of FCC crystal type between the first plate of HCP crystal type and the third plate of BCC crystal type can it be possible to realize the deep corrugated structure at the interface between the first plate and the second plate, and the second plate and the third plate. In order to realize the deep corrugated structure at the interface, it is necessary to start from the rolling process, thickness setting and the strength of the second plate, and work together to obtain the deep corrugated structure. This structure makes the deformation of the composite material more coordinated, and the atoms at the interface diffuse more fully. The thickness of the second plate affects the stress state and interface atomic diffusion during rolling. If the second plate is too thick, the deformation is not coordinated and the atomic diffusion is insufficient under large reduction, and there is a possibility of interface tearing. If the second plate is too thin, the first plate may pierce the second plate, resulting in a decrease in interlayer bonding strength and electrical conductivity.
[0030] It should be pointed out that the smallest unit in the present application can be a structure of the first plate|the second plate|the third plate. Although the different materials on both sides during the rolling process will cause bending deformation of the rolled composite material, it does not affect the formation of a deep corrugated structure at the interface between the first plate and the second plate and the second plate and the third plate. The present application implements an annealing process for the first plate, the second plate, and the third plate, and can set the corresponding annealing temperature and holding time based on the actual material selection. This technology is common knowledge and can be obtained from existing literature.
[0031] The minimum unit is preheated before rolling, and is coated with aluminum foil at a holding temperature of 150-350°C for 15-35 minutes. Preheating before rolling reduces rolling stress and increases the fluidity of the metal, and aluminum foil is used to prevent oxidation of the stacked plates.
[0032] The first plate is one or more of AZ31, AZ91, ZK60 / 61, and Mg-RE series alloy plates; and / or, the second plate is one or more of copper or copper alloys; and / or, the third plate is tantalum. It should be noted that the first plate is an existing well-known material and is not the invention of the present invention; copper and copper alloys use existing materials, but their strength and crystal form need to meet the limited conditions of this application; the third plate uses pure tantalum plate to improve radiation resistance.
[0033] The minimum unit is arranged in the following manner: first plate|second plate|third plate|second plate|first plate. The symmetrical arrangement can reduce or eliminate deformation curling caused by inconsistent deformation on both sides of the composite material during rolling. The first plates can be the same or different materials, such as the first plates are all AZ31, i.e., AZ31|Cu|Ta|Cu|AZ31, or the first plates are AZ31 and AZ91, i.e., AZ31|Cu|Ta|Cu|AZ91.
[0034] After rolling the minimum unit, on the one hand, rolling is continued to prepare a layered composite material with excellent performance, but the number of layers is 5, and the subsequent rolling of the minimum unit is no more than two times, and the single reduction is 10%-20%. On the other hand, the minimum unit after the first rolling is stacked and then rolled, and the stacking and rolling are repeated no more than five times, and the reduction of the rolling is 50%-65%, so as to increase the number of layers of the prepared layered composite material and improve the radiation resistance. Specifically, the first rolling: the minimum unit is stacked and rolled, and the number of layers is 10; the second rolling: continue to stack and roll, and the number of layers is 20; the third rolling: continue to stack and roll, and the number of layers is 40. Through the subsequent rolling and rolling, the probability of the generation of micro-corrugated structure continues to increase, and the micro-corrugated structure generated by the subsequent rolling can bring at least 10% increase in tear strength. However, the number of subsequent rolling passes, the amount of single reduction, and the number of stacking and overlapping rolling need to be strictly controlled to improve the tear strength of the layered composite material while avoiding excessive rolling that may cause internal cracks, or too few rolling times and too little reduction that may result in the ineffective generation of the microscopic corrugated structure, resulting in low bonding strength.
[0035] As a preferred embodiment, the minimum unit after the first rolling is stacked at 90 degrees and then rolled, and the stacking and rolling are repeated for no more than five times, and each time the stacking is 90 degrees, and the stacking reduction is 55%-65%. Compared with other stacking methods, the microscopic corrugated structure generated by stacking at 90 degrees is richer, so that the tear strength is increased by at least 5% compared with other stacking methods.
[0036] The rolling speed of the first rolling, subsequent rolling and lap rolling is 0.015-0.05 m / s, and the roller temperature is 150-350° C. The rolling speed is related to the heat generation speed during the rolling process. The rolling speed and the roller temperature are strictly controlled so that the mechanical bonding strength between the interfaces of the layered composite materials during the rolling process can be optimized, and the local temperature is prevented from being too high, which reduces the generation of micro-corrugated structures, and the local temperature is prevented from being too low, which leads to a decrease in deformation capacity.
[0037] Furthermore, the surface of the composite material after the first rolling or the previous rolling is polished before rolling, and then heated in a vacuum environment or an inert gas atmosphere at a temperature of 300-350°C for a holding time of 10-20 minutes, thereby reducing the oxide on the surface of the composite material and improving the mechanical bonding strength of the interface to be bonded after lamination.
[0038] The first plate and the third plate after annealing are polished, including rolling and transverse polishing, and the transverse and longitudinal surface roughness Ra after polishing is 5-15μm. Although the present invention can use the crystal type, strength, thickness and rolling process between the plates to prepare a bonding interface with a deep corrugated structure, the increase in surface roughness can increase the macroscopic contact area of the plate interface and improve the interlayer bonding strength of the layered composite material, but the second plate is thinner, and the probability of breakpoints or tearing during the rolling process is high, resulting in a significant reduction in the bonding strength between the first plate and the second plate. Therefore, the surface roughness of the first plate and the second plate is limited, and the surface roughness is not too small so that the strengthening effect is not obvious, and affects the generation of the microscopic corrugated structure. The roughness should not be too large, which will increase the probability of breakpoints and tearing.
[0039] Preferably, the first rolling pass, subsequent rolling passes and lap rolling are performed in a vacuum or inert gas atmosphere.
[0040] The embodiment of the present invention further provides a layered composite material, which is prepared by the above-mentioned preparation method.
[0041] Since the layered composite materials prepared in this application are used in deep space environments, high radiation, drastic temperature changes and other environments, the test contents include:
[0042] DSC test: heat from room temperature to 500°C at a rate of 20°C / s, keep warm for 1h, and check whether there is cracking at the magnesium-copper-tantalum interface.
[0043] Mechanical properties test: The yield strength and tensile strength of the plate are tested using national standards.
[0044] Interface bonding strength: By applying tension on both sides of the prepared layered composite material, the minimum tension applied when tearing is the interface bonding strength.
[0045] Conductivity test: The conductivity is tested according to the national standard. The prepared layered composite material is sampled longitudinally and tested by applying electricity at both ends.
[0046] In order to further illustrate the present invention, the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0047] Example 1
[0048] The embodiment of the present invention provides a method for preparing a layered composite material and a layered composite material, wherein the preparation method comprises:
[0049] S1 stacks the annealed AZ31B plate (first plate), Cu foil (second plate) and Ta plate (third plate) to form a minimum unit, wherein the Cu foil is located between the AZ31B plate and the Ta plate; the tensile strength of the Cu foil is 220 MPa; the thickness of the AZ31B plate is 1 mm, the thickness of the Cu foil is 0.1 mm, and the thickness of the Ta plate is 0.5 mm.
[0050] The surfaces of the AZ31B plate and the Ta plate were polished along the rolling direction and the transverse direction respectively. The transverse and longitudinal surface roughness Ra after polishing was 5-15 μm. After polishing, the Ta plate, AZ31B plate and Cu foil were cleaned with anhydrous ethanol and then vacuum dried.
[0051] The pretreated plates are stacked in the order of AZ31B|Cu|Ta|Cu|AZ31B, fixed at both ends by electric welding or rivets, and then placed in a heating furnace at a holding temperature of 350°C for 30 minutes.
[0052] S2 stacks the preheated AZ31B|Cu|Ta|Cu|AZ31B, with a first rolling reduction of 65%, a roll temperature of 280°C, and a rolling rate of 0.02 m / s.
[0053] The first stack rolling: use an angle grinder to perform surface treatment on the smallest unit after the first rolling to remove the oxide layer and impurity layer, then cut it into two pieces of equal length from 1 / 2 of the smallest unit, stack the two plates, fix them with electric welding or rivets, and then place them in a heating furnace for insulation at a temperature of 350°C for 15 minutes; stack the plates, with a roller temperature of 280°C, a reduction of 50%, and a rolling rate of 0.02m / s.
[0054] Second lamination: Use an angle grinder to perform surface treatment on the composite material after the first lamination to remove the oxide layer and the impurity layer, then cut it into two pieces of equal length from 1 / 2 of the composite material, stack the two pieces of composite material, fix them with electric welding or rivets, and then place them in a heating furnace for insulation at a temperature of 350°C for 15 minutes; Lamination the above-mentioned plates, with a roller temperature of 280°C, a reduction of 50%, and a rolling rate of 0.02 m / s.
[0055] Finally, the rolled plate is surface treated with an angle grinder to remove the oxide layer and the impurity layer, thereby obtaining a layered composite plate with a minimum unit of AZ31B|Cu|Ta|Cu|AZ31B, which contains 20 layers of magnesium, copper and tantalum.
[0056] In the DSC test, the prepared layered composite sheet was heated from room temperature to 500 °C and kept at this temperature for 1 h. There was no cracking at the magnesium-copper-tantalum interface. Figure 1 shown.
[0057] The mechanical properties, electrical conductivity and thermodynamic tests were carried out on the above-mentioned plates. The results showed that the prepared plates had a tensile yield strength of 343.17 MPa, a tensile strength of 377.98 MPa, and an elongation of 6.5%; an interface bonding strength of 65 MPa, and a room temperature conductivity of 28±3 KS / mm.
[0058] Example 2
[0059] The embodiment of the present invention provides a method for preparing a layered composite material and a layered composite material, wherein the preparation method comprises:
[0060] S1 stacks the annealed AZ31B sheet (first sheet), Cu foil (second sheet) and Ta sheet (third sheet) to form a minimum unit, wherein the Cu foil is located between the AZ31B sheet and the Ta sheet; the tensile strength of the Cu foil is 220 MPa; the thickness of the AZ31B sheet is 1 mm, the thickness of the Cu foil is 0.05 mm, and the thickness of the Ta sheet is 0.7 mm.
[0061] The surfaces of the AZ31B plate and the Ta plate were polished along the rolling direction and the transverse direction respectively. The transverse and longitudinal surface roughness Ra after polishing was 5-15 μm. After polishing, the Ta plate, AZ31B plate and Cu foil were cleaned with anhydrous ethanol and then vacuum dried.
[0062] The pretreated plates are stacked in the order of AZ31B|Cu|Ta|Cu|AZ31B, fixed at both ends by electric welding or rivets, and then placed in a heating furnace at a holding temperature of 350°C for 30 minutes.
[0063] S2 stacks the preheated AZ31B|Cu|Ta|Cu|AZ31B, with a first rolling reduction of 60%, a roll temperature of 150°C, and a rolling rate of 0.02 m / s.
[0064] The first stack rolling: use an angle grinder to perform surface treatment on the smallest unit after the first rolling to remove the oxide layer and impurity layer, then cut it into two pieces of equal length from 1 / 2 of the smallest unit, stack the two plates, fix them with electric welding or rivets, and then place them in a heating furnace for insulation at a temperature of 350°C for 20 minutes; stack the plates, with a roller temperature of 150°C, a reduction of 50%, and a rolling rate of 0.02m / s.
[0065] Second lamination: Use an angle grinder to perform surface treatment on the composite material after the first lamination to remove the oxide layer and the impurity layer, then cut it into two pieces of equal length from 1 / 2 of the composite material, stack the two pieces of composite material, fix them with electric welding or rivets, and then place them in a heating furnace for insulation at a temperature of 350°C for 15 minutes; Lamination the above-mentioned plate with a roller temperature of 150°C, a reduction of 50%, and a rolling rate of 0.02 m / s.
[0066] Finally, the rolled plate is surface treated with an angle grinder to remove the oxide layer and the impurity layer, thereby obtaining a layered composite plate with a minimum unit of AZ31B|Cu|Ta|Cu|AZ31B, which contains 20 layers of magnesium, copper and tantalum.
[0067] DSC test shows that there is no cracking at the magnesium-copper-tantalum interface when the temperature rises from room temperature to 500°C. The prepared sheet has a tensile yield strength of 301.4MPa, a tensile strength of 340.31MPa, and an elongation of 6%; the interface bonding strength is 56MPa, and the room temperature conductivity is 28±3KS / mm.
[0068] Example 3
[0069] The embodiment of the present invention provides a method for preparing a layered composite material and a layered composite material, wherein the preparation method comprises:
[0070] S1 stacks the annealed AZ31B plate (first plate), Cu foil (second plate) and Ta plate (third plate) to form a minimum unit, wherein the Cu foil is located between the AZ31B plate and the Ta plate; the tensile strength of the Cu foil is 220 MPa; the thickness of the AZ31B plate is 10 mm, the thickness of the Cu foil is 0.5 mm, and the thickness of the Ta plate is 7.5 mm.
[0071] The surfaces of the AZ31B plate and the Ta plate were polished along the rolling direction and the transverse direction respectively. The transverse and longitudinal surface roughness Ra after polishing was 5-15 μm. After polishing, the Ta plate, AZ31B plate and Cu foil were cleaned with anhydrous ethanol and then vacuum dried.
[0072] The pretreated plates are stacked in the order of AZ31B|Cu|Ta|Cu|AZ31B, fixed at both ends by electric welding or rivets, and then placed in a heating furnace at a holding temperature of 150°C for 35 minutes.
[0073] S2 stacks the preheated AZ31B|Cu|Ta|Cu|AZ31B, with a first rolling reduction of 60%, a roll temperature of 150°C, and a rolling rate of 0.015 m / s.
[0074] The first stack rolling: use an angle grinder to perform surface treatment on the smallest unit after the first rolling to remove the oxide layer and impurity layer, then cut it into two pieces of equal length from 1 / 2 of the smallest unit, stack the two plates, fix them with electric welding or rivets, and then place them in a heating furnace for insulation at a temperature of 350°C for 20 minutes; stack the plates, with a roller temperature of 150°C, a reduction of 50%, and a rolling rate of 0.015m / s.
[0075] Finally, the rolled plate is surface treated with an angle grinder to remove the oxide layer and the impurity layer, thereby obtaining a layered composite plate with a minimum unit of AZ31B|Cu|Ta|Cu|AZ31B, which contains 10 layers of magnesium, copper and tantalum.
[0076] DSC test shows that there is no cracking at the magnesium-copper-tantalum interface when the temperature rises from room temperature to 500°C. The prepared sheet has a tensile yield strength of 178.5MPa, a tensile strength of 280MPa, and an elongation of 6%; an interface bonding strength of 51MPa, and a room temperature conductivity of 31±2KS / mm.
[0077] Example 4
[0078] The embodiment of the present invention provides a method for preparing a layered composite material and a layered composite material, wherein the preparation method comprises:
[0079] S1 stacks the annealed AZ31B sheet (first sheet), Cu foil (second sheet) and Ta sheet (third sheet) to form a minimum unit, wherein the Cu foil is located between the AZ31B sheet and the Ta sheet; the tensile strength of the Cu foil is 220 MPa; the thickness of the AZ31B sheet is 2 mm, the thickness of the Cu foil is 0.1 mm, and the thickness of the Ta sheet is 1 mm.
[0080] The surfaces of the AZ31B plate and the Ta plate were polished along the rolling direction and the transverse direction respectively. The transverse and longitudinal surface roughness Ra after polishing was 5-15 μm. After polishing, the Ta plate, AZ31B plate and Cu foil were cleaned with anhydrous ethanol and then vacuum dried.
[0081] The pretreated plates are stacked in the order of AZ31B|Cu|Ta|Cu|AZ31B, fixed at both ends by electric welding or rivets, and then placed in a heating furnace at a holding temperature of 300°C for 30 minutes.
[0082] S2 stacks the preheated AZ31B|Cu|Ta|Cu|AZ31B, with a first rolling reduction of 50%, a roll temperature of 300°C, and a rolling rate of 0.015 m / s.
[0083] The first stack rolling: use an angle grinder to perform surface treatment on the smallest unit after the first rolling to remove the oxide layer and impurity layer, then cut it into two pieces of equal length from 1 / 2 of the smallest unit, stack the two plates, fix them with electric welding or rivets, and then place them in a heating furnace for insulation at a temperature of 300°C for 15 minutes; perform stack rolling on the above plates, with a roller temperature of 300°C, a reduction of 50%, and a rolling rate of 0.05m / s.
[0084] Second rolling: Use an angle grinder to perform surface treatment on the composite material after the first rolling to remove the oxide layer and the impurity layer, then cut it into two pieces of equal length from 1 / 2 of the composite material, stack the two plates, fix them with electric welding or rivets, and then place them in a heating furnace for insulation at a temperature of 300°C for 15 minutes; roll the above plates at a roller temperature of 300°C, a reduction of 50%, and a rolling rate of 0.05 m / s.
[0085] The third lamination rolling: the composite material after the second lamination rolling is surface treated with an angle grinder to remove the oxide layer and the impurity layer, and then cut into two pieces of equal length from 1 / 2 of the composite material, stack the two plates, fix them with electric welding or rivets, and then place them in a heating furnace for insulation at a temperature of 300°C for 15 minutes; the above plates are lamination rolled with a roller temperature of 300°C, a reduction of 50%, and a rolling rate of 0.05 m / s.
[0086] Finally, the rolled plate is surface treated with an angle grinder to remove the oxide layer and the impurity layer, thereby obtaining a layered composite plate with a minimum unit of AZ31B|Cu|Ta|Cu|AZ31B, which contains 40 layers of magnesium, copper and tantalum.
[0087] DSC test shows that there is no cracking at the magnesium-copper-tantalum interface when the temperature rises from room temperature to 500°C. The prepared sheet has a tensile yield strength of 150MPa, a tensile strength of 280MPa, an elongation of 6%, an interface bonding strength of 46.83MPa, and a room temperature conductivity of 26±2KS / mm.
[0088] Example 5
[0089] The embodiment of the present invention provides a method for preparing a layered composite material and a layered composite material, wherein the preparation method comprises:
[0090] S1 stacks the annealed ZK61 sheet (first sheet), Cu foil (second sheet) and Ta sheet (third sheet) to form a minimum unit, wherein the Cu foil is located between the ZK61 sheet and the Ta sheet; the tensile strength of the Cu foil is 220 MPa; the thickness of the ZK61 sheet is 10 mm, the thickness of the Cu foil is 0.8 mm, and the thickness of the Ta sheet is 6 mm.
[0091] The surfaces of the ZK61 plate and the Ta plate were polished along the rolling direction and the transverse direction respectively. The transverse and longitudinal surface roughness Ra after polishing was 5-15 μm. After polishing, the Ta plate, ZK61 plate and Cu foil were cleaned with anhydrous ethanol and then vacuum dried.
[0092] The pretreated plates are stacked in the order of ZK61|Cu|Ta|Cu|ZK61, fixed at both ends by electric welding or rivets, and then placed in a heating furnace at a holding temperature of 350°C for 15 minutes.
[0093] S2 stacks the preheated ZK61|Cu|Ta|Cu|ZK61, with a first rolling reduction of 60%, a roll temperature of 350°C, and a rolling rate of 0.02 m / s.
[0094] The first stack rolling: use an angle grinder to perform surface treatment on the smallest unit after the first rolling to remove the oxide layer and impurity layer, then cut it into two pieces of equal length from 1 / 2 of the smallest unit, stack the two plates, fix them with electric welding or rivets, and then place them in a heating furnace for insulation at a temperature of 350°C for 15 minutes; perform stack rolling on the above plates, with a roller temperature of 350°C, a reduction of 50%, and a rolling rate of 0.02m / s.
[0095] Finally, the rolled plate is surface treated with an angle grinder to remove the oxide layer and the impurity layer, thereby obtaining a layered composite plate with a minimum unit of ZK61|Cu|Ta|Cu|ZK61, which contains 10 layers of magnesium, copper and tantalum.
[0096] DSC test, from room temperature to 500 ℃, there is no cracking at the magnesium-copper-tantalum interface. Figure 2 The prepared sheet has a tensile yield strength of 200 MPa, a tensile strength of 280 MPa, an elongation of 6%, an interface bonding strength of 62 MPa, and a room temperature electrical conductivity of 45±3 KS / mm.
[0097] Example 6
[0098] The embodiment of the present invention provides a method for preparing a layered composite material and a layered composite material, wherein the preparation method comprises:
[0099] S1 stacks the annealed ZK61 plate (first plate), Cu foil (second plate) and Ta plate (third plate) to form a minimum unit, wherein the Cu foil is located between the ZK61 plate and the Ta plate; the tensile strength of the Cu foil is 220 MPa; the thickness of the ZK61 plate is 5 mm, the thickness of the Cu foil is 0.5 mm, and the thickness of the Ta plate is 3 mm.
[0100] The surfaces of the ZK61 plate and the Ta plate were polished along the rolling direction and the transverse direction respectively. The transverse and longitudinal surface roughness Ra after polishing was 5-15 μm. After polishing, the Ta plate, ZK61 plate and Cu foil were cleaned with anhydrous ethanol and then vacuum dried.
[0101] The pretreated plates are stacked in the order of ZK61|Cu|Ta|Cu|ZK61, fixed at both ends by electric welding or rivets, and then placed in a heating furnace at a holding temperature of 300°C for 30 minutes.
[0102] S2 stacks the preheated ZK61|Cu|Ta|Cu|ZK61, with a first rolling reduction of 60%, a roll temperature of 250°C, and a rolling rate of 0.02 m / s.
[0103] The first stack rolling: use an angle grinder to perform surface treatment on the smallest unit after the first rolling to remove the oxide layer and impurity layer, then cut it into two pieces of equal length from 1 / 2 of the smallest unit, stack the two plates, fix them with electric welding or rivets, and then place them in a heating furnace for insulation at a temperature of 250°C for 15 minutes; perform stack rolling on the above plates, with a roller temperature of 250°C, a reduction of 50%, and a rolling rate of 0.02m / s.
[0104] Second lamination: Use an angle grinder to perform surface treatment on the composite material after the first lamination to remove the oxide layer and the impurity layer, then cut it into two pieces of equal length from 1 / 2 of the composite material, stack the two plates, fix them with electric welding or rivets, and then place them in a heating furnace for insulation at a temperature of 250°C for 15 minutes; perform lamination on the plates, with a roller temperature of 250°C, a reduction of 50%, and a rolling rate of 0.02 m / s.
[0105] The third lamination: the composite material after the second lamination is surface treated with an angle grinder to remove the oxide layer and the impurity layer, and then cut into two pieces of equal length from 1 / 2 of the composite material, stack the two plates, fix them with electric welding or rivets, and then place them in a heating furnace for insulation at a temperature of 250°C for 15 minutes; the above plates are lamination-rolled, with a roller temperature of 250°C, a reduction of 50%, and a rolling rate of 0.02 m / s.
[0106] Fourth rolling: Use an angle grinder to perform surface treatment on the composite material after the third rolling to remove the oxide layer and the impurity layer, then cut it into two pieces of equal length from 1 / 2 of the composite material, stack the two plates, fix them with electric welding or rivets, and then place them in a heating furnace for insulation at a temperature of 250°C for 15 minutes; roll the above plates at a roller temperature of 250°C, a reduction of 50%, and a rolling rate of 0.02 m / s.
[0107] The fifth rolling: the composite material after the fourth rolling is surface treated with an angle grinder to remove the oxide layer and the impurity layer, and then cut into two pieces of equal length from 1 / 2 of the composite material, stack the two plates, fix them with electric welding or rivets, and then place them in a heating furnace for insulation at a temperature of 250°C for 15 minutes; the above plates are rolled, with a roller temperature of 250°C, a reduction of 50%, and a rolling rate of 0.02 m / s.
[0108] Finally, the rolled plate was surface treated with an angle grinder to remove the oxide layer and the impurity layer, and a layered composite plate with a minimum unit of AZ31B|Cu|Ta|Cu|AZ31B was obtained, which contained 160 layers of magnesium, copper and tantalum.
[0109] DSC test shows that there is no cracking at the magnesium-copper-tantalum interface when the temperature rises from room temperature to 500°C. The prepared sheet has a tensile yield strength of 200MPa, a tensile strength of 280MPa, an elongation of 6%, an interface bonding strength of 46.83MPa, and a room temperature conductivity of 38±3KS / mm.
[0110] Example 7
[0111] The embodiment of the present invention provides a method for preparing a layered composite material and a layered composite material, wherein the preparation method comprises:
[0112] S1 stacks the annealed AZ31B plate (first plate), Cu foil (second plate) and Ta plate (third plate) to form a minimum unit, wherein the Cu foil is located between the AZ31B plate and the Ta plate; the tensile strength of the Cu foil is 220 MPa; the thickness of the AZ31B plate is 1 mm, the thickness of the Cu foil is 0.1 mm, and the thickness of the Ta plate is 0.5 mm.
[0113] The surfaces of the AZ31B plate and the Ta plate were polished along the rolling direction and the transverse direction respectively. The transverse and longitudinal surface roughness Ra after polishing was 5-15 μm. After polishing, the Ta plate, AZ31B plate and Cu foil were cleaned with anhydrous ethanol and then vacuum dried.
[0114] The pretreated plates are stacked in the order of AZ31B|Cu|Ta|Cu|AZ31B, fixed at both ends by electric welding or rivets, and then placed in a heating furnace at a holding temperature of 350°C for 30 minutes.
[0115] S2 stacks the preheated AZ31B|Cu|Ta|Cu|AZ31B, with the first rolling pass having a reduction of 50%, a roll temperature of 150°C, and a rolling rate of 0.015 m / s; followed by a second rolling pass with a reduction of 10%, a roll temperature of 150°C, and a rolling rate of 0.015 m / s; and finally a third rolling pass with a reduction of 10%, a roll temperature of 150°C, and a rolling rate of 0.015 m / s.
[0116] Finally, the rolled plate was surface treated with an angle grinder to remove the oxide layer and the impurity layer, thereby obtaining a layered composite plate with the minimum unit of AZ31B|Cu|Ta|Cu|AZ31B.
[0117] DSC test shows that there is no cracking at the magnesium-copper-tantalum interface when the temperature rises from room temperature to 500°C. The prepared sheet has a tensile yield strength of 210MPa, a tensile strength of 306MPa, an elongation of 6%, an interface bonding strength of 57.5MPa, and a room temperature conductivity of 32±2KS / mm.
[0118] Example 8
[0119] The embodiment of the present invention provides a method for preparing a layered composite material and a layered composite material, wherein the preparation method comprises:
[0120] S1 stacks the annealed AZ31B sheet (first sheet), Cu foil (second sheet) and Ta sheet (third sheet) to form a minimum unit, wherein the Cu foil is located between the AZ31B sheet and the Ta sheet; the tensile strength of the Cu foil is 220 MPa; the thickness of the AZ31B sheet is 1 mm, the thickness of the Cu foil is 0.1 mm, and the thickness of the Ta sheet is 0.5 mm.
[0121] The surfaces of the AZ31B plate and the Ta plate were polished along the rolling direction and the transverse direction respectively. The transverse and longitudinal surface roughness Ra after polishing was 5-15 μm. After polishing, the Ta plate, AZ31B plate and Cu foil were cleaned with anhydrous ethanol and then vacuum dried.
[0122] The pretreated plates are stacked in the order of AZ31B|Cu|Ta|Cu|AZ31B, fixed at both ends by electric welding or rivets, and then placed in a heating furnace at a holding temperature of 350°C for 30 minutes.
[0123] S2 stacks the preheated AZ31B|Cu|Ta|Cu|AZ31B, with the first rolling pass having a reduction of 75%, a roll temperature of 350°C, and a rolling rate of 0.05 m / s; followed by a second rolling pass with a reduction of 20%, a roll temperature of 350°C, and a rolling rate of 0.05 m / s; and finally a third rolling pass with a reduction of 20%, a roll temperature of 350°C, and a rolling rate of 0.05 m / s.
[0124] Finally, the rolled plate was surface treated with an angle grinder to remove the oxide layer and the impurity layer, thereby obtaining a layered composite plate with the minimum unit of AZ31B|Cu|Ta|Cu|AZ31B.
[0125] DSC test shows that there is no cracking at the magnesium-copper-tantalum interface when the temperature rises from room temperature to 500°C. The prepared sheet has a tensile yield strength of 278MPa, a tensile strength of 345MPa, an elongation of 8%, an interface bonding strength of 67MPa, and a room temperature conductivity of 29±2KS / mm.
[0126] Example 9
[0127] Different from Example 1, in this embodiment, during the stacking process of stacking, the smallest unit after the first rolling is stacked at 90° and then stacked, and the stacking and rolling are repeated, each time at 90°, and the reduction during the stacking process is 60%.
[0128] DSC test shows that there is no cracking at the magnesium-copper-tantalum interface when the temperature rises from room temperature to 500°C. The prepared sheet has a tensile yield strength of 345MPa, a tensile strength of 425MPa, an elongation of 8%, an interface bonding strength of 75MPa, and a room temperature conductivity of 39±3KS / mm.
[0129] Comparative Example 1
[0130] Different from Example 1, no Cu foil is added to the layered composite material in this comparative example.
[0131] The prepared layered composite materials are Figure 3 As shown, it can be seen that Mg / Ta rolled plate has delamination phenomenon and cannot achieve effective bonding.
[0132] Comparative Example 2
[0133] Different from Example 1, this comparative example adopts a cold rolling process, that is, there is no need for preheating, heat preservation, and setting of the roller temperature.
[0134] The prepared layered composite materials are Figure 4 As shown in Figs. 4a and 4b, it can be seen that the Mg / Cu / Ta / Cu / Mg rolled plate has serious stratification and produces a large number of surface cracks and cracks, and cannot be effectively combined, indicating that the selection of appropriate heating temperature and rolling temperature is the key factor for the successful preparation of the multi-interface scattering loss electromagnetic shielding composite plate in the present invention.
[0135] Comparative Example 3
[0136] Different from Example 1, in this comparative example, the thickness of the AZ31B plate is 0.8 mm, the thickness of the Cu foil is 0.04 mm, and the thickness of the Ta plate is 0.4 mm.
[0137] In the interface of the prepared layered composite material, the Cu layer is partially penetrated. The prepared plate has a tensile yield strength of 136MPa, a tensile strength of 185MPa, an elongation of 5%, and an interface bonding strength of 26MPa.
[0138] Comparative Example 4
[0139] Different from Example 1, in this comparative example, the thickness of the AZ31B plate is 12 mm, the thickness of the Cu foil is 0.9 mm, and the thickness of the Ta plate is 6 mm.
[0140] In the DSC test, the magnesium-copper-tantalum interface cracked after the temperature was raised from room temperature to 500°C and kept warm for 30 minutes; at the same time, the prepared sheet had a tensile yield strength of 136MPa, a tensile strength of 156MPa, an elongation of 4%, and an interface bonding strength of 31MPa.
[0141] Comparative Example 5
[0142] Different from Example 1, in this comparative example, the Cu foil is replaced by Al foil. Its tensile strength is 45MPa
[0143] DSC test shows that when the temperature rises from room temperature to 500℃, the interface cracks and there is no microscopic corrugated structure on the interface. The prepared sheet has a tensile yield strength of 145MPa, a tensile strength of 225MPa, an elongation of 7%, and an interface bonding strength of 28MPa.
[0144] Comparative Example 6
[0145] Different from Example 1, in this comparative example, the thickness of the AZ31B plate is 2.2 mm, the thickness of the Cu foil is 0.1 mm, and the thickness of the Ta plate is 0.5 mm.
[0146] DSC test shows that the magnesium-copper-tantalum interface cracks when the temperature rises from room temperature to 500°C. The prepared sheet has a tensile yield strength of 166MPa, a tensile strength of 235MPa, an elongation of 6%, and an interface bonding strength of only 28MPa.
[0147] Comparative Example 7
[0148] Different from Example 1, in this comparative example, the thickness of the AZ31B plate is 1 mm, the thickness of the Cu foil is 0.1 mm, and the thickness of the Ta plate is 1 mm.
[0149] DSC test shows that the magnesium-copper-tantalum interface cracks when the temperature rises from room temperature to 500°C. The prepared sheet has a tensile yield strength of 171MPa, a tensile strength of 243MPa, an elongation of 6%, and an interface bonding strength of 31MPa.
[0150] Comparison between Example 1 and Comparative Examples 1-2 shows that a reasonable rolling process combined with the addition of Cu foil can be rolled into a layered composite material, and cold rolling or direct rolling cannot effectively composite the various plates. By comparing Example 1 with Comparative Examples 3-4, it can be seen that the thickness of the Cu foil is too thin, resulting in partial penetration of the Cu layer, resulting in low bonding strength of the layered composite material and cracking of the magnesium-copper-tantalum interface in the DSC test; while the Cu foil is thicker, the microscopic corrugated structure cannot be effectively generated during the subsequent rolling process, resulting in cracking of the magnesium-copper-tantalum interface in the subsequent DSC test. By comparing Example 1 with Comparative Examples 5-7, it can be seen that the strength of the second plate and the thickness setting between the layers affect the subsequent deep corrugated structure, resulting in a reduction in the generation rate of macro or micro corrugated structures.
[0151] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a layered composite material, characterized in that: The steps include: The annealed first plate, the second plate and the third plate are stacked to form a minimum unit, wherein the crystal structure of the first plate is an HCP structure, the second plate is an FCC structure, the third plate is a BCC structure, and the second plate is located between the first plate and the third plate; The tensile strength of the second plate is 150-300 MPa; The thickness ratio of the first plate, the second plate and the third plate satisfies 20:(1-2):(10-15), and the thickness of the second plate is 0.05-0.80 mm; The minimum unit is rolled, and the reduction amount of the first rolling is 50%-75%.
2. The preparation method according to claim 1, characterized in that: The minimum unit is preheated before rolling, and is coated with aluminum foil at a holding temperature of 150-350° C. for a holding time of 15-35 minutes.
3. The preparation method according to claim 1, characterized in that: The first plate is one or more of AZ31, AZ91, ZK60 / 61, and Mg-RE series alloy plates; And / or, the second plate material is one or more of copper or copper alloy; And / or, the third plate material is tantalum.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The minimum unit is arranged in the following order: first plate | second plate | third plate | second plate | first plate.
5. The preparation method according to claim 4, characterized in that: The minimum unit is subjected to subsequent rolling for no more than two times, and the single rolling reduction is 10%-20%; The minimum units after the first rolling are stacked and then rolled together, and the stacking and rolling are repeated for no more than five times, and the reduction amount of the rolling together is 50%-65%.
6. The preparation method according to claim 5, characterized in that: The smallest unit after the first rolling is stacked at 90 degrees and then rolled, and the stacking is repeated for no more than five times and each time is stacked at 90 degrees, and the stacking reduction is 55%-65%.
7. The preparation method according to claim 5 or 6, characterized in that: The rolling speeds of the first rolling pass, subsequent rolling passes and overlapping rolling are 0.015-0.05 m / s, and the rolling roll temperature is 150-350°C.
8. The preparation method according to claim 5 or 6, characterized in that: Before rolling, the surface of the composite material of the first rolling or the previous rolling is polished, and then heated in a vacuum environment or an inert gas atmosphere, with a heating temperature of 300-350° C. and a holding time of 10-20 minutes.
9. The preparation method according to claim 1, characterized in that: The first plate and the third plate after annealing are ground, including rolling direction and transverse direction grinding, and the transverse and longitudinal surface roughness Ra after grinding is 5-15 μm.
10. A layered composite material, characterized in that: The layered composite material is prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Mg-Al-Ta composite board with good interface bonding and preparation method
CN115740002A
Boron carbide reinforced Mg-Al-Ta layered composite board and preparation method thereof
CN115742485A
Anti-electron-radiation multilayer structure shielding material and preparation method thereof
CN112599271A
Lightweight high-strength Mg-Al-Ta composite metal plate and rolling forming method thereof
CN113733685A
Method for forming a nickel-based layered structure on a magnesium alloy substrate, a surface-treated magnesium alloy article made therefrom, and a cleaning solution and a surface treatment solution used therefor
US20070269677A1
Cited By
Explosive welding method for preparing anti-radiation metal composite material and metal composite material
CN120516155A
Explosive welding method for preparing radiation-proof metal composite material and metal composite material
CN120516155B